Hearing Loss in Iraq Deteriorates Social and Environmental Quality of Life: Gangguan Pendengaran di Irak Memperburuk Kualitas Hidup Sosial dan Lingkungan - Sarah Abed Alsada; Nuha Adel Ibrahim (Academia Open, 2024)
This study investigates the impact of hearing loss on social interactions and environmental behaviors in individuals, utilizing a descriptive method at the Otolaryngology Department of Al-Diwaniyah Teaching Hospital, Iraq, with 200 participants from December 25, 2023, to March 1, 2024. Participants underwent pure tone audiometry and completed the WHO Quality of Life-BREF (WHOQOL-BREF) Version in Arabic. Results indicate a moderate decline in social and environmental quality of life among those with hearing loss, highlighting the necessity for targeted interventions to improve outcomes. This study underscores the need for regular auditory screenings and enhanced support services to better the quality of life for individuals suffering from hearing loss. Highlights: Quality of Life: Hearing loss significantly impacts social and environmental interactions. Intervention Need: Highlights the necessity for targeted interventions to improve life quality. Screening Importance: Emphasizes regular auditory screenings to detect and manage hearing loss early. Keywords: Hearing Loss, Social Interaction, Environmental Behavior, Quality of Life, Auditory Health